Analysis of Transformational Leadership, Work Culture, and Innovation on Improving the Performance of the State Civil Apparatus of Fakfak Regency - Sri Ambarwati Setioningrum; Sundjoto Sundjoto; Pompong. B. Setiadi; Rifda Fitranti (Research Trend in Technology and Management, 2024)
A leader who inspires his employees and puts aside personal interests for the good of an organization is needed in improving the performance of the State civil apparatus and accompanied by the behavior of the work culture and innovation owned by the employees will help in the process of achieving an organizational goal. The research aims to analyze transformational leadership, work culture and innovation towards improving the performance of the State civil apparatus in Fakfak district. The research was carried out during September – October 2023. Descriptive research method with a combination of quantitative and qualitative analysis approaches. Data was obtained through a direct survey of respondents who had been deliberately determined. The data obtained are given a weight value based on the assessment indicators obtained from the results of the preliminary research. The validity and reliability of the data were tested gradually and in a structured manner using the triangulation and role sharing approaches. The results of the study are presented in the form of a spider web diagram equipped with an illustration of the shift share gap value, and a regression equation model obtained from the SPSS statistical device version 2.3.